The poisonwood bible : a novel - Kingsolver, Barbara (New York : HarperPerennial, 1999)
The tale of one family's tragic undoing and remarkable reconstruction over the course of three decades in post-colonial Africa. An evangelical minister discovers that everything--from garden seeds to Scripture--is transformed on African soil.
Includes bibliographical references.
Keywords: CONGO -- DEMOCRATIC REPUBLIC